Diversify, produce or buy? An analysis of factors contributing to household dietary diversity among shrimp and non-shrimp farmers in coastal Bangladesh - Amelie Bernzen; Ellen Mangnus; Franziska Sohns (Food Security, 2022)
Until the Covid-19 pandemic, Bangladesh had reported consistent improvements regarding its food and nutrition security (FNS) status, and yet, the country still features poor FNS outcomes among parts of its population. In rural coastal regions of the Ganges–Brahmaputra-Meghna delta, farming households' vulnerability is particularly exacerbated by a range of environmental hazards, increasing challenges for agriculture to contribute to higher FNS levels. In the context of existing literature on the trade-offs between subsistence agriculture and cash-earning livelihood activities, vis-à-vis food and nutrition security outcomes, this article assesses the relative contribution of crop diversification vis à vis other factors on the households' Food Consumption Score (FCS) in specific livelihood contexts. We provide differentiated analyses between primarily export-oriented shrimp farming and non-shrimp farming households, so policy makers can better address FNS targets. Quantitative data from 1,188 sample households across the delta were analysed through descriptive and linear regression analyses. Results show that households cultivating shrimp have a significantly higher dietary diversity than households that do not. Among shrimp farmers, crop diversification has the relatively strongest significant positive effect on dietary diversity, suggesting part of the aquacultural crops are geared towards subsistence. By contrast, crop diversification seems to have a negative effect on dietary diversity among households that do not produce shrimp, especially when different agricultural crops are combined. Importantly, both for shrimp and non-shrimp farmers, crop diversification systems combining agriculture with aquaculture, and agroforestry seem to improve diverse diets among households. While by no means a panacea to solving FNS challenges among rural households, we suggest that promoting specific crop diversification systems could be a beneficial pathway to improved FNS outcomes.
Keywords: 630; Food and nutrition security; Dietary diversity; Crop diversification; Farmer livelihoods; Aquaculture; Coastal Bangladesh